1996
DOI: 10.1007/bf02336662
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial expression patterns of two G-protein coupled receptors inDrosophila melanogaster

Abstract: Temporal and spatial expression patterns of a muscarinic acetylcholine receptor (Acr60C) and an octopamine/tyramine receptor (Octyr) were determined in Drosophila melanogaster using quantitative Northern analysis and in situ hybridization to tissue sections. Expression of mRNA encoding both of these G-protein coupled receptors peaks initially in 18 to 21 hour embryos following the formation of the mature larval nervous system. Levels of mRNA then decline during larval stages, rising to a second peak in 3 to 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 83 publications
3
15
1
Order By: Relevance
“…If tyramine, rather than octopamine, were an excitatory modulator, we would not expect the M18 flies to jump less far or generate less force, as they have higher levels of tyramine than the wild types. Jumping in Drosophila Although hono gene expression has previously only been found in the adult central nervous system (Arakawa et al, 1990;Saudou et al, 1990;Hannan and Hall, 1996;Kutsukake et al, 2000), our data indicate a role for hono in the adult peripheral nervous system, specifically at the TDT neuromuscular junction. An explanation for our observations of reductions in jumping distance and force in hono is that octopamine action at the neuromuscular junction is blocked.…”
Section: Discussioncontrasting
confidence: 48%
“…If tyramine, rather than octopamine, were an excitatory modulator, we would not expect the M18 flies to jump less far or generate less force, as they have higher levels of tyramine than the wild types. Jumping in Drosophila Although hono gene expression has previously only been found in the adult central nervous system (Arakawa et al, 1990;Saudou et al, 1990;Hannan and Hall, 1996;Kutsukake et al, 2000), our data indicate a role for hono in the adult peripheral nervous system, specifically at the TDT neuromuscular junction. An explanation for our observations of reductions in jumping distance and force in hono is that octopamine action at the neuromuscular junction is blocked.…”
Section: Discussioncontrasting
confidence: 48%
“…The remaining imaginal discs for the wings and appendages showed no expression of DmDopEcR. DmDopEcR appears to be diffusely expressed in the adult Drosophila CNS (data not shown), similar to other insect aminergic receptors (Hannan and Hall, 1986).…”
Section: Expression Pattern Of Dmdopecrmentioning
confidence: 75%
“…Whole-mount in situ hybridizations to wild-type Oregon R Drosophila melanogaster embryos and larvae were performed as described previously (Hannan and Hall, 1986), using the formaldehyde fixation procedure. RNA probes were prepared from a pBluescript SK II(ϩ) plasmid containing the full-length DmDopEcR receptor after linearization with BamHI (antisense) and XhoI (sense) and after gel purification.…”
Section: Methodsmentioning
confidence: 99%
“…Tyramine receptor transcripts can be detected at early stages of insect development (Vanden Broeck et al, 1995;Hannan and Hall, 1996;Ohta et al, 2003) and repeated injection of tyramine into locust larvae is reported to delay ecdysis and reduce locust viability (Torfs et al, 2000). In the fruit fly, levels of tyramine receptor expression fluctuate during embryonic, larval, and pupal development (Hannan and Hall, 1996), and in the silkworm developmental changes in tyramine levels have also been identified (Hirashima et al, 1999).…”
mentioning
confidence: 97%
“…In the fruit fly, levels of tyramine receptor expression fluctuate during embryonic, larval, and pupal development (Hannan and Hall, 1996), and in the silkworm developmental changes in tyramine levels have also been identified (Hirashima et al, 1999). The honey bee tyramine receptor gene, Amtyr1, is widely expressed in the brain of the adult worker bee (Blenau et al, 2000), but whether it is expressed in the developing brain is unknown.…”
mentioning
confidence: 98%